Hydrogen Storage in Partially Exfoliated Magnesium Diboride Multilayers. Issue 6 (5th December 2022) - Gunda, Harini; Ray, Keith G.; Klebanoff, Leonard E.; Dun, Chaochao; Marple, Maxwell A. T.; Li, Sichi; Sharma, Peter; Friddle, Raymond W.; Sugar, Joshua D.; Snider, Jonathan L.; Horton, Robert D.; Davis, Brendan C.; et al.
Abstract: Metal boride nanostructures have shown significant promise for hydrogen storage applications. However, the synthesis of nanoscale metal boride particles is challenging because of their high surface energy, strong inter‐ and intraplanar bonding, and difficult‐to‐control surface termination. Here, it is demonstrated that mechanochemical exfoliation of magnesium diboride in zirconia produces 3–4 nm ultrathin MgB2 nanosheets (multilayers) in high yield. High‐pressure hydrogenation of these multilayers at 70 MPa and 330 °C followed by dehydrogenation at 390 °C reveals a hydrogen capacity of 5.1 wt%, which is ≈50 times larger than the capacity of bulk MgB2 under the same conditions. This enhancement is attributed to the creation of defective sites by ball‐milling and incomplete Mg surface coverage in MgB2 multilayers, which disrupts the stable boron–boron ring structure. The density functional theory calculations indicate that the balance of Mg on the MgB2 nanosheet surface changes as the material hydrogenates, as it is energetically favorable to trade a small number of Mg vacancies in Mg(BH4 )2 for greater Mg coverage on the MgB2 surface. The exfoliation and creation of ultrathin layers is a promising new direction for 2D metal boride/borohydride research with the potential to achieve high‐capacity reversible hydrogen storage at more moderate pressures and temperatures. Abstract : Ultrathin 4 nm magnesium diboride multilayers are synthesized using a simple mechanochemical approach and display enhanced reactivity toward dihydrogen at 70 MPa and 330 °C. Simulations and experiments reveal that exfoliation disrupts the stable boron–boron ring structure, while during hydrogenation it becomes energetically favorable to trade a small number of Mg vacancies in Mg(BH4 )2 for greater surface Mg coverage in MgB2 .